Child labor - Morrow, V (Wiley, 2015)
There is no agreed definition of “child labor” because the concept is a culturally relative construct, operable primarily in the original English and lost in translation to most other languages. Thus, “child labor” carries different meanings or connotations. In the social sciences, the term usually refers to work that is in some way harmful to children or impedes their development. There is also a legal definition of the term to refer to work that is undertaken below the minimum age set for employment, whether such work is harmful or beneficial to children; this definition is more concerned with labor-force work. Western conceptualizations of “work” and “labor” equate work with paid employment, but sociologists and social anthropologists have long argued that work can be broadly understood as the performance of necessary tasks and the production of necessary values, and includes domestic work and unpaid family based labor.